3-D Structural Modeling of Meyal Field, Potwar Sub-basin, Pakistan using Seismic and Well Data - Mehmood, W.; Aadil, N.; Jadoon, Y. K. (The Nucleus, 2016)
Meyal Field is located near Pindi Gheb, District Attock in Upper Indus Basin, Pakistan. In this paper, 2-D seismic and well data of Meyal-17 is interpreted to construct a 3-D structural model using the Kingdom Interpretation Software Suite. After identifying the horizons on seismic lines with the integration of well and seismic data, faults were mapped. With the help of fault polygons, time contour maps were generated which were then converted to velocity and depth contour maps. Finally, 3-D structural model was generated from these maps. It is interpreted that there are two possible structural traps which are suitable for accumulation of hydrocarbons in the study area. One is present in the southwestern part of the Field with two fault bounded closure and the other is one fault assisted in the central part as indicated with dotted circles A and B respectively. Closures on depth contour maps of two fault bounded trap are 777 m, 845 m, 752 m and 750 m at the level of top Kohat, top Sakesar, top Lockhart and top Datta respectively. While, closures of one fault assisted trap are 150 m, 250 m, 200 m and 250 m at the level of top Kohat, top Sakesar, top Lockhart and top Datta respectively. The closure due to down thrown block is smaller than closure due to two faults (F2 & F3) in the southwestern part of the field. 3-D Model shows that all four horizons are confirmable at one another.